(untitled) (Jurnal De Jure Muhammadiyah Cirebon, 2025)
The crimes that occur today do not look at ho the perpetrators are. Many perpetrators are minors. The government itself has issued las governing the juvenile justice system, namely law number 11 of 2012. The series of investigative processes that children will receive are certainly not much different from the adult process, but the courts will be held in private. Islam itself has prohibited its people from committing crimes, so this also makes Islam a reference in providing punishment for child offenders ho are minors. Keywords: Child, Criminal Law, Islamic Law